# How do you solve 7( 2x - 1) = 5( x - 14)?

Mar 7, 2018

$x = - 7$

#### Explanation:

Expand the brackets

$14 x - 7 = 5 x - 70$

Subtract $5 x$ from both sides

$9 x - 7 = - 70$

Add $7$to both sides

$9 x = - 63$

Divide both sides by $9$

$x = - 7$

Mar 7, 2018

$x = - 7$

#### Explanation:

$7 \left(2 x - 1\right) = 5 \left(x - 14\right)$

Distribute and multiply $7$ to $2 x$ and $- 1$ to get

$14 x - 7 =$

Then distribute and multiply $5$ to $x$ and $- 14$ to get

$= 5 x - 70$

Put together, it will look like this

$14 x - 7 = 5 x - 70$

Then add $70$ to $- 70$ and $- 7$ to get

$14 x + 63 = 5 x$

Then subtract $14 x$ from $14 x$ and $5 x$ to get

$63 = - 9 x$

Divide by $- 9$ on both sides to get

$- 7 = x$

Mar 7, 2018

See solution below:

#### Explanation:

First expand out the brackets:
$7 \left(2 x - 1\right) = 14 x - 7$
and
$5 \left(x - 14\right) = 5 x - 70$

Hence, the equation becomes:
$14 x - 7 = 5 x - 70$

Now rearrange to make $x$ the subject:

1. Subtract $5 x$ from both sides to obtain:
$\implies 14 x - 5 x - 7 = 5 x - 5 x - 70$
$\implies 9 x - 7 = 70$

2. Then add 7 to both sides to isolate $x$
$\implies 9 x - 7 + 7 = - 70 + 7$
$\implies 9 x = - 63$

3. Finally, divide both sides by 9 to obtain $x$
$\implies x = - \frac{63}{9}$

Hence,
$x = - 7$